Provirophages in the Bigelowiella genome bear testimony to past encounters with giant viruses - Blanc, Guillaume (Proc Natl Acad Sci U S A, 2015)
Virophages are recently discovered double-stranded DNA virus satellites that prey on giant viruses (nucleocytoplasmic large DNA viruses; NCLDVs), which are themselves parasites of unicellular eukaryotes. This coupled parasitism can result in the indirect control of eukaryotic cell mortality by virophages. However, the details of such tripartite relationships remain largely unexplored. We have discovered ∼300 predicted genes of putative virophage origin in the nuclear genome of the unicellular alga Bigelowiella natans. Physical clustering of these genes indicates that virophage genomes are integrated into the B. natans genome. Virophage inserts show high levels of similarity and synteny between each other, indicating that they are closely related. Virophage genes are transcribed not only in the sequenced B. natans strain but also in other Bigelowiella isolates, suggesting that transcriptionally active virophage inserts are widespread in Bigelowiella populations. Evidence that B. natans is also a host to NCLDV members is provided by the identification of NCLDV inserts in its genome. These putative large DNA viruses may be infected by B. natans virophages. We also identify four repeated elements sharing structural and genetic similarities with transpovirons—a class of mobile elements first discovered in giant viruses—that were probably independently inserted in the B. natans genome. We argue that endogenized provirophages may be beneficial to both the virophage and B. natans by (i) increasing the chances for the virophage to coinfect the host cell with an NCLDV prey and (ii) defending the host cell against fatal NCLDV infections.